Evaluation of competence training for the minimally trained health worker in type 2 diabetes: A cluster randomized controlled trial. Issue 44 (30th October 2020) - Gudlavalleti, Anirudh Gaurang; Babu, Giridhara R.; van Schayck, Onno C.P.; Schaper, Nicolaas C.; Lewis, Melissa Glenda; Murthy, G.V.S.
Abstract: Introduction: Type 2 diabetes mellitus is responsible for high mortality and morbidity globally and in India. India has high prevalence of the condition and the burden is set to increase exponentially in the next decade. Indians traditionally reside in rural or semi-urban areas with limited access to healthcare facilities. To overcome this, the government has introduced a cadre of health workers called Accredited Social Health Activists (ASHA) for such areas. These workers were initially trained to provide maternal & infant care but now need improved competence training to improve type 2 diabetes screening & management in these locations. The objective of the study is to assess the competence training provided to ASHA workers at the chosen study sites. Methodology: A cluster randomized control trial has been designed. It will be conducted across 8 centers in Hyderabad & Rangareddy districts of Telangana, India. The training will be provided to ASHA workers. The tool used for training will be developed from existing sources with an emphasis on topics which require training. The training will be delivered across 6 months at each center as a classroom training. Each participant's baseline competence will be recorded using a questionnaire tool and a practical evaluation by trained public health experts. The same experts will use the same tools to assess the training post the intervention. Discussion: This trial will evaluate the use of health worker training as a tool for improving the clinical competence in relation to type 2 diabetes mellitus. We anticipate that the module will provide a greater understanding of type 2 diabetes mellitus, the importance of screening of both disease and complications and improved skills for the same. The study has received the ethical approval form the Institutional Ethics Committee of the Indian Institute of Public Health Hyderabad. The registration number is: IIPHH/TRCIEC/218/2020. The trial has also been registered under the Clinical trial registry of India (CTRI) on 27 th July 2020. The registration number of the trial is: CTRI/2020/07/026828. The URL of the registry trial is: http://ctri.nic.in/Clinicaltrials/showallp.php?mid1=45342&EncHid=&userName=CTRI/2020/07/026828 . Abstract : Supplemental Digital Content is available in the text